Impact of prophylactic cavotricuspid isthmus ablation in atrial fibrillation recurrence after a first pulmonary vein isolation procedure. (15th May 2018) - Mesquita, João; Ferreira, António Miguel; Cavaco, Diogo; Carmo, Pedro; Madeira, Márcio; Freitas, Pedro; Costa, Francisco Moscoso; Morgado, Francisco; Mendes, Miguel; Adragão, Pedro
Abstract: Introduction: PVI is a well-established therapy for patients with drug refractory atrial fibrillation (AF). However, it remains unclear whether prophylactic cavotricuspid isthmus (CTI) ablation at the time of PVI improves long-term freedom from AF. Objective: To compare the outcomes of patients who underwent PVI alone vs. PVI + prophylactic CTI ablation. Methods: Propensity score (PS) matching analysis based on a registry dataset of 1931 consecutive patients who underwent a first AF catheter ablation. After excluding those with documented/inducible atrial flutter (n = 233), 1698 individuals were available for matching. Following adjustment for age, gender, body mass index (BMI), hypertension, smoking, diabetes, LA volume, type of AF, and type of navigation (magnetic vs. manual), PS matched 411 patients who underwent PVI + CTI ablation with 411 receiving PVI alone. Results: PS analysis yielded a study population of 822 matched patients (58 ± 11 years, 69% males, 64% with paroxysmal AF). Over a median 2 years follow-up period there were 278 AF recurrences (34%). Survival free of AF (Log rank p = .965) and annual relapse rates were similar in the two groups - 10.9%/year vs 10.1%/year (PVI vs PVI + CTI, respectively, p = .97). CTI ablation remained unassociated with AF-free survival (HR 1.09, 95%CI: 0.84–1.41, p = .54) after Cox regression adjustment for age, sex, type of AF, LA volume, hypertension, diabetes, BMI and center. Female gender, current smoking, indexed LA volume and non-paroxysmal AF were identified as independent predictors of relapse after matching. Conclusions: Prophylactic CTI ablation at the time of a first PVI does not seem to improve long-term freedom from AF. Highlights: Prophylactic CTI ablation at the time of a first PVI does not improve long-term freedom from AF. Large multicenter observational registry data assessed using propensity score matching.